A circle with centre
O
1
and radius
2
r
is drawn. A point
O
2
is taken
at a distance
r
from
O
1
. Now a circle is drawn with centre
O
2
and
radius
r
. Now two lines are drawn from
O
2
each making an angle
6
0
0
with
O
1
O
2
produced and the given figure is obtained.
If the area of the shaded region in the given figure can be written as A = k r 2 then find ⌊ 1 0 0 k ⌋ .
Note: The starting part of the question is just a description of how the figure is drawn. The figure must be taken as the reference for finding the shaded region.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You can use double integral in polar coordinates to find the shaded area
There's a typo - ∠ P O 1 O 2 = 6 0 ∘ ... You had in mind a different angle. great proof otherwise.
Very complex solution
Log in to reply
Actually this question was intended to have a complex solution. There is no easier way to do this
Yes, this is nonlinear curve (quadratic curve), and does not have direct relationship with either smaller or larger circle. Both the circle share some information related to the shaded region. It is part of the larger circle (2r) and resulted as an extension of the radius of smaller circle (r) with 120-degree angle at the center (O2). So, it is not direct, it has to be complex. Thanks for the solution!
I came up with this solution but the one with obtuse triangle is much easier. Area of sector of bigger circle subtracted by the sum of sector of the other circle and twice the area of the triangle.
I didn't get it how the angle PO1O2 = 60? I should be 30.
A should be easily equal to: \frac{1}{6} \times S {O1} - \frac{1}{3} \times S {O2} - \frac{2}{3} \times S_{O1PQ}
could have assumed equations for circles and lines and then integrated to find area
In my solution I used Trigonometry:
Area(shaded) = AS1(O1,2r,2b)) - AS2(O2,r,2a) - 2At(O1O2P);
AS2(O2,r,2a0) = (a0)r^2 = (1/3)Pi*r^2,
a0 = (1/3)Pi half angle of the sector S2;
Let (R;A) a sistem of a polar coordinates on the plane with center O2,
axis y, so:
x = 0, is for O1O2, (segment of axis y)
so y = 0, is perpendicular to axis y with positive values to right side;
Let P, Q; P1, Q1 the intersection points between left and right rays
from O1, and Circle(O1,2r) and Circle(O2,r) rispectively;
L, L1 the intersection between perpendicular to x axis from Q, Q1,
and M the intersection between O2P an perpendicular to O2P and
O2P; c = angle(Q1O1Q); d = angle(O1QO2)
we have: Pi/2 - A = 2(Pi/2 - (B + c)), so:
B = (Pi/2 + A - 2c)/2, and
d = B - A, so: d = (Pi/2 - A -2c)/2;
R^2 = x^2 + y^2;
Translating from O2 in O1 we have a sistem of polar coordinates
(R',B), with axis X,Y so that for Circle(O1,2r):
X = (2r)cosB = x;
Y = (2r)sinB;
X = x;
Y = y + r;
Equation of Circle(O2,r):
Equation of Circle(O1,2r): .
x^2 + y^2 + 2ry + r^2 = 4r^2 x = (2r)cosB;
y + r = (2r)sinB;
y = r(2sinB -1);
x^2 + y^2 = 3r^2 -2ry =>
R^2 = (r^2)(5 - 4sinB);
R = r√(5 - 4sinB)
now we have for the sines theorem applied to triangle(O1O2P):
O1P/sin(Pi/2 + A) = O1O2/sin(d), =>
2r/cosA = r/√((1-sin(A + 2c))/2);
(i had applied some trigonometry identities),
sin(A + 2c) = (1 - (1/2)(cosA)^2),
which leads to:
A + 2c = asin(1 - (1/2)(cosA)^2);
A - 2c = 2A - asin(1 - (1/2)(cosA)^2);
sinB = sin((Pi/2 + A - 2c)/2) =
sinB = √(1 + sin(2A - asin(1 - (1/2)(cosA)^2))),
(note: B > 0); so for A0 = Pi/2 - Pi/3 = Pi/6,
sinB0 = sqrt((1 + sin(Pi/3 - asin(5/8)))/2) = 0,825693909,
B0 = 0,971431172 rad;
b0 = Pi/2 - B0 = 0.599365154 rad,
AS1(O1,2r,2b0) = b0 (2r)^2 = 4b0r^2 = 2,397460617 r^2
AS2(O2,2r,(2/3)Pi) = (1/3)Pi = 1.047197551*r^2
2At(O1O2P) = 2(1/2)|O1P||O2M| = 2(r^2)sin(b0) =
2(r^2)sin(b0) = 2At(O1P2P) = 1.128236797*r^2;
Ash = 0.222026269(r^2) = k(r^2) =>
k = 0.222026269;
ceil(100k) = 22
Yeah! Same method , just I considered the triangle O X 1 O X 2 P to find a and then θ !
I used the sine law to determine an angle first. The geometry becomes elementary thereafter.
Of course I myself have done like that
∵
o
f
s
y
m
m
e
t
r
y
,
w
e
s
h
a
l
l
o
n
l
y
c
o
n
s
i
d
e
r
t
h
e
r
i
g
h
t
h
a
l
f
.
E
x
t
e
n
d
O
1
O
2
t
o
m
e
e
t
t
h
e
c
i
r
c
l
e
s
a
t
A
.
S
m
a
l
l
c
i
r
c
l
e
r
a
d
i
u
s
O
2
C
m
a
k
e
s
∠
6
0
o
w
i
t
h
A
O
2
.
E
x
t
e
n
d
O
2
C
t
o
m
e
e
t
b
i
g
c
i
r
c
l
e
a
t
B
.
A
p
p
l
y
i
n
g
S
i
n
R
u
l
e
t
o
△
O
1
O
2
B
,
∠
O
2
B
O
1
=
S
i
n
−
1
{
(
r
∗
S
i
n
1
2
0
o
)
/
(
2
r
)
}
=
2
5
.
6
6
o
.
∠
O
2
O
1
B
=
6
0
−
2
5
.
6
6
=
3
4
.
3
4
o
.
A r e a A B O 1 = A r e a A B ′ O 1
\color\red {The ~Area~ABC = Area~ ABO_{1} -Area~O_{1}O_{2}B-Area~ACO_2}
\color\red {Area~ ABO_1} = 34.34^o/360^o * \pi * (2r)^2 =\color\green{ \boxed {1.199 * r^2}}
So~the~\color\red{Area~O_{1}O_{2}B} = \frac{1}{2} * (2r) * (r * Sin34.34^o) = \color\green{ \boxed {0.564 * r^2}}.
\color\red {Area~ ACO_2} = 60^o/360^o * \pi * r^2 = \color\green{ \boxed {0.523 * r^2}}
\color\green {shaded ~Area~ABC = 1.199 - 0.564 - 0.523 =.112 * r^2 }
A = ⌊ 1 0 0 ∗ 2 ∗ . 1 1 2 ⌋ = 2 2
how do you get 34.34 degrees?
Log in to reply
It is given. But now I have change the order to make it clear.
Problem Loading...
Note Loading...
Set Loading...
Let the 2 r -arc of the shaded area to end at points P and Q . The required area A = A 1 area of the sector O 1 P Q − A 2 area of 3 1 of the smaller circle − A 3 area of the two similar triangles △ O 1 O 2 P and △ O 1 O 2 Q .
To find A 1 and A 3 we need to know ∠ P O 1 O 2 = ∠ Q O 1 O 2 = θ . Let the line P Q meet the extension of O 1 O 2 at R . Let O 2 R , P R and O 2 P be a , b and c respectively.
Since ∠ P O 1 O 2 = 6 0 ∘ , b = 3 a and c = 2 a . We know that O 1 R 2 + P R 2 = O 1 P 2 .
⟹ ( r + a ) 2 + b 2 ( r + a ) 2 + ( 3 a ) 2 r 2 + 2 a r + a 2 + 3 a 2 4 a 2 + 2 r a − 3 r 2 = ( 2 r ) 2 = ( 2 r ) 2 = 4 r 2 = 0
Solving the quadratic equation for a , we have a = 4 1 3 − 1 r . Then cos θ = 2 r a + r = 0 . 8 2 5 6 9 3 9 0 9 , and θ = c o s − 1 0 . 8 2 5 6 9 3 9 0 9 = 0 . 5 9 9 3 6 5 1 5 4 rad. Now,
A = A 1 − A 2 − A 3 = k r 2
A 1 = 2 2 θ ( 2 r ) 2 = 4 θ r 2 = 2 . 3 9 7 4 6 0 6 1 7 r 2
A 2 = 3 1 π r 2 = 1 . 0 4 7 1 9 7 5 5 1 r 2
A 3 = 2 r ( 2 1 b ) = 3 a r = 1 . 1 2 8 2 3 6 7 9 8 r 2
⇒ A = ( 2 . 3 9 7 4 6 0 6 1 7 − 1 . 0 4 7 1 9 7 5 5 1 − 1 . 1 2 8 2 3 6 7 9 8 ) r 2 = 0 . 2 2 2 0 2 6 2 6 8 r 2
⇒ k = 0 . 2 2 2 0 2 6 2 6 8
⇒ ⌊ 1 0 0 k ⌋ = 2 2